A viable model for power focusing in a lossy cylinder. - Nabulsi, K.A.
In this paper, we are interested in controlling the power dissipation within a homogeneous lossy cylinder of finite length when a field is applied to the surface of the cylinder. The fields are assumed to be independent of the azimuthal angle. To begin, a field which satisfies the required dissipation inside the cylinder is assumed on the axis of the lossy cylinder. An analytical evaluation of the continuous source on the surface of the cylinder can then be carried out. This is an inverse problem where the response is known and the source is to be determined. A realization of the continuous source (surface field) in terms of a discrete array is also given. Results are presented that show an excellent agreement between the actual continuous sources and the discrete array in producing the field on the axis of the lossy cylinder. In fact, a small number of slots (fifteen or less) produce accurate agreement for the required field on the axis of the cylinder. Bioelectromagnetics and hyperthermia treatment of cancer in cylindrical objects such as limbs and torsos is one potential application. Nondestructive testing of manufactured cylindrical products is another one where the energy is focused in a given region in the cylinder
Keywords: EM radiation; EM wave propagation; Bioelectromagnetics; Cancer; Continuous source; Cylinder surface; Cylindrical objects; Discrete array; Energy focusing; Finite length; Homogeneous lossy cylinder; Hyperthermia treatment; Inverse problem; Limbs; Manufactured cylindrical products; Nondestructive testing; Power dissipation control; Power focusing; Slots; Surface field; Torsos; Viable model